ANALISIS DATA FORENSIK INVESTIGASI KASUS PEREDARAN NARKOBA PADA SMARTPHONE BERBASIS ANDROID - Novi Saputri; Rini Indrayani (Djtechno: Jurnal Teknologi Informasi, 2022)
Along with the development of Smartphone technology, especially Android-based which is a communication tool whose features develop from time to time with a total of 89.2% of users, which is also followed by an increase in users of the WhatsApp Instant Messaging Platform. WhatsApp is one of the most popular social media in the world with a total of 2.20 billion users. On the other hand, WhatsApp is often used as a medium of crime (cybercrime) such as the case of narcotics trafficking, whose transactions are carried out online by sending messages, pictures, videos, locations and so on. The purpose of this study is to find forensic evidence and to compare two tools using the (Without Root Access) and (Root Access) approaches, using the NIJ (National Institute of Justice) method. The results of the extraction were then analyzed using the forensic tools Magnet Axiom without Rooting access managed to obtain data extraction of 33.33% while MobilEdit forensics was equal to a total of 33.33%. While the comparison with Rooting access, Magnet Axiom obtained greater data extraction as much as 77.77% and MobilEdit Forensic as much as 66.66%. The results of the study based on the scenario used, it can be concluded that the recommended tool is Magnet Axiom because it has better performance